IMPROVING EIGHTH GRADERS’ FUNCTIONAL READING ACHIEVEMENT THROUGH COLLABORATIVE STRATEGIC READING (CSR) - HAFSAH RIZQIYAH; MACHDALENA VIANTY; ERLINA ERLINA (Sriwijaya University Learning and Education International Conference, 2016)
The objectives of this study were (1) to find out whether or not there was asignificant difference in students’ functional reading achievement before and afterthey were taught through Collaborative Strategic Reading (CSR) and (2) to find outwhether or not there was a significant difference in functional reading achievementbetween the students who were taught through CSR and those who were not. Thisstudy was a quasi-experimental research method that applied non-equivalent controlgroup research design. The population of this study was the eighth grade students ofone of the junior high schools in Palembang in academic year 2015 - 2016 and thenumber of sample was 76 students, that was selected by using purposive samplingtechnique. The data of this study were collected by using a pre-test and a post-testand were analyzed statistically by using paired and independent sample t-test. Theresults of this study revealed that (1) there was a significant difference in students’functional reading achievement before and after they were taught through CSR(mean diff=18.87, and ρ-value=.000) and (2) there was a significant difference infunctional reading achievement between the students who were taught through CSRand those who were not (mean diff=12.11, and ρ-value=.000). Therefore, it can beconcluded that CSR is effective in improving the students' functional readingachievement.